QUALIMAMA: an assessment tool for mammography services quality - Costa, Mariane Oliveira; Fausto, Agnes Fonseca; Velasco, Fermin Garcia; Furquim, Tania Aparecida; Mol, Anderson William; Luzardo, Francisco Martinez (Scientia Plena, 2016)
The objective of this research was to develop and validate a system of indicators to audit the overall quality of mammography services that includes the factors related to the image, dose and environment settings, applying it for the characterization of these services in two cities of southern Bahia-Brazil. It was proposed a new quality indicator system for mammography called QUALIMAMA, based in the main current regulatory documents: the guides of the International Atomic Energy Agency- IAEA (2009 and 2011), the European Guide (2006), the Ordinances MS 453/98, MS 2898/2013 and 306 RDC/ANVISA. The QUALIMAMA was applied to evaluate 5 clinics in the micro region of Ilhéus-Itabuna, pointing precisely insufficiencies in these services, which may be impacting on the incidence rates of breast cancer in the region, and will serve as a basis for the improvement of mammography services in the assessed clinics. We compared the results obtained in the application of the proposed system with the assessments carried out based on the main regulatory documents prevailing in the world. The system showed a high level of integration of indicators, allowing a more complete picture of the quality in its various dimensions.